COVID-19-Infektion – Risiko für thrombembolische Komplikationen - Zerwes, S. (Gefasschirurgie, 2020)
While the COVID-19 syndrome triggered by the SARS CoV‑2 was initially seen predominantly as a pulmonary disease, the number of reports of vascular complications has recently increased. The aim of the present review article is to summarize the most relevant vascular complications in COVID-19 patients. These include venous and arterial thromboembolic events as well as local thromboses, which can form directly on the endothelium at the site of cytokine release. A generalized coagulopathy also appears to promote this thrombogenic condition. With a rate of approximately 20%, deep vein thrombosis (DVT) of the leg is one of the most common thromboembolic events in COVID-19 patients requiring intensive care treatment. In addition, arterial events, such as stroke or acute coronary syndrome were also observed in COVID-19 patients with pre-existing vascular disease. Children rarely have vascular complications, but a systemic immune response similar to the Kawasaki syndrome and toxic shock syndrome has been reported. According to current data, the risk of thromboembolic events in hospitalized COVID-19 patients is significantly increased, making thrombosis prophylaxis with low molecular weight or unfractionated heparin necessary. If pharmaceutical thrombosis prophylaxis is contraindicated, intermittent pneumatic compression should be used. In addition, in patients admitted to the hospital with suspected or proven SARS-CoV‑2 infection, the determination of D‑dimers and, in the case of positive results, broad indication for compression sonography of the deep leg veins are recommended. This allows to detect and treat DVT at an early stage. The treatment of thromboses should be carried out according to current guidelines with therapeutic anticoagulation. Further studies and registries are needed to improve the understanding of the relationship between COVID-19 infection and the occurrence of thromboembolic events.